A Study of Organelles Associated with Vitellogenesis in Oncomelania Hupensis Quadrasi, A Molluscan Host of Schictosoma Japonicum - F.G Claveria; F.J Etges (Universitas Gadjah Mada, 1988)
A Study of Organelles Associated with Vitellogenesis in Oncomelania Hupensis Quadrasi, A Molluscan Host of Schictosoma Japonicum